Pemetaan SMK Di Jawa Barat, Bangka Belitung dan Kalimantan Tengah - Mulyadi, Yadi; Mukhidin, Mukhidin; Setiawan, Agus; Hamdani, Aam; Purnawan, Purnawan (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2010)
Since 2005 the Directorate of Vocational High School Development (Direktorat PSMK) has launched a national program of vocational high school (SMK) development on a large scale with the scenario of increasing the quantity vocational high school students and reducing the number of senior high school students (SMA) or known by the scheme of 70:30. Its fundamental consideration is to reduce the unemployment rate of SMA graduates can who not continue to studies to their further higher level of education. While the development of vocational education is expected to expand the employment absorption in the greater world of industry. The implications to the above national program significance of the increasing numbers of new SMK spreading from both in urban and rural . Some of both public and private vocational schools has emerged quickly, even in some areas there are primary school, junior or vocational school used to make the CMS. This condition is certainly worrying, on the one side it is line with the national program but on the other side the increase in quantity does not linearly correlate with the quality. More over the relevence of the SMK competence program has not been thoroughly examined an in depth study that can give an impact on the employment absorption in the world of indutry. Aperiodically comprehensive mapping of the all existing vocational the schools need tobe done ranging especially from the availability of the teachers the program expertise as well as the and the infrastructure as well as development of the students, including the increasing the number of teachers, the interest of the community as well as programs being carried out in SMK. The method used in conducting the research is a descriptive method, this method describes the condition of the existing vocational schools in each subject study area. Data is collected through using the census method and documentation methods. This research has produced data for all three subject study areas in West Java, Bangka Belitung and Central Kalimantan and has sequentially resulted as follows: (1) Number of SMK: 1043, 43, 67, (2) Number learning group: 9454, 418, 446, (3) Number of learning resource centre: 134 988, 5782, 5764, (4) Number of Students: 327,757, 14,482, 14,010, (5) Number of graduates: 81 916, 2517, 2586.